The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.21037/tau.2017.05.14
|View full text |Cite
|
Sign up to set email alerts
|

Optimising patient outcomes with photoselective vaporization of the prostate (PVP): a review

Abstract: Benign prostatic hyperplasia (BPH) is a common pathology causing lower urinary tract symptoms (LUTS) and may significantly impact quality of life. While transurethral resection of the prostate (TURP) remains the gold standard treatment, there are many evolving technologies that are gaining popularity. Photoselective vaporization of the prostate (PVP) is one such therapy which has been shown to be non-inferior to TURP. We aimed to review the literature and discuss factors to optimise patient outcomes in the set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Liang et al 9 found that the risk of bleeding complications was 2.58 times greater in men treated with TURP who were taking anticoagulants or antiplatelets than not, but that those treated with HoLEP or photoselective vapourisation of the prostate (PVP), such as GreenLight, had a bleeding risk that was not significantly different from the control group. Albisinni et al 16 concluded that laser prostate vapourisation or enucleation with GreenLight PVP or HoLEP was safe in frail, elderly men, while Pascoe et al 17 found no increase in complications after PVP in men with prostates larger than 100 mL compared with in those with smaller glands, although operative time and retreatment rates were higher. In general, systematic reviews of high-risk men with benign prostatic hyperplasia concur that all available interventions have comparable efficacy, particularly with IPSS, Qmax, and PVR outcomes, but that laser enucleation and vapourisation therapies have a more favourable perioperative profile, in terms of length of stay, blood loss, and catheterisation time.…”
Section: Discussionmentioning
confidence: 99%
“…Liang et al 9 found that the risk of bleeding complications was 2.58 times greater in men treated with TURP who were taking anticoagulants or antiplatelets than not, but that those treated with HoLEP or photoselective vapourisation of the prostate (PVP), such as GreenLight, had a bleeding risk that was not significantly different from the control group. Albisinni et al 16 concluded that laser prostate vapourisation or enucleation with GreenLight PVP or HoLEP was safe in frail, elderly men, while Pascoe et al 17 found no increase in complications after PVP in men with prostates larger than 100 mL compared with in those with smaller glands, although operative time and retreatment rates were higher. In general, systematic reviews of high-risk men with benign prostatic hyperplasia concur that all available interventions have comparable efficacy, particularly with IPSS, Qmax, and PVR outcomes, but that laser enucleation and vapourisation therapies have a more favourable perioperative profile, in terms of length of stay, blood loss, and catheterisation time.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-established that TURP is effective in improving LUTSs and maintains its efficacy in the long-term [ 8 ]. Other surgical alternatives to TURP have been introduced, including holmium enucleation of the prostate (HoLEP), photoselective vaporization of the prostate (PVP), and bipolar transurethral resection in saline [ 9 , 10 , 11 ]. However, most conventional transurethral procedures have several disadvantages.…”
Section: Introductionmentioning
confidence: 99%
“…Gastroenterologists have used LTV to treat esophageal and rectal cancer [8,9]. In order to achieve desired clinical outcomes, various lasers have been evaluated through ex vivo, in vivo, and clinical studies to compare tissue removal capability, hemostasis, perioperative complications, and postoperative complications [3,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, LTV is expected to remove tissue efficiently with excellent hemostasis and minimal collateral tissue damage, which can reduce hospitalization time and complications [12][13][14]. For the best clinical outcomes, the surgeons are often trained and required to control the power density over the tissue during surgery by adjusting the distance between the catheter tip and the tissue surface, keeping a constant sweeping speed of the catheter, and closely monitoring the tissue responses to laser vaporization.…”
Section: Introductionmentioning
confidence: 99%